Structural and optical properties of heteroepitaxial beta Ga2O3 films grown on MgO (100) substrates - Kong, Lingyi; Ma, Jin; Luan, Caina; Mi, Wei; Lv, Yu (Thin solid films, 2012)
Gallium oxide (Ga2O3) films were deposited on MgO (100) substrates by metalorganic vapor phase epitaxy. Structure analyses showed that the films deposited at 550–700°C were epitaxial β-Ga2O3 films with an out of plane relationship of β-Ga2O3(100)||MgO(100). The film deposited at 650°C showed the best crystallinity and the microstructure of the film was investigated by high resolution transmission electron microscopy. A theoretical model of the growth mechanism was proposed and the in-plane epitaxial relationship was given to be β-Ga2O3[001]||MgO . A four-domain structure inside the epitaxial film was clarified. The β-Ga2O3 film deposited at 650°C showed an absolute average transmittance of 95.9% in the ultraviolet and visible range, which had an optical band gap of 4.87eV. ► Beta Ga2O3 epitaxial films were deposited on MgO(100) substrate. ► A theoretical model of the growth mechanism was proposed. ► The transmittance of the film in the ultraviolet and visible region exceeded 95.9%.